Efektivitas metode Baca Tulis Qur’an (BTQ) dalam meningkatkan kemampuan membaca Al-Qur’an siswa SMA Islam: The effectiveness of the Qur’an reading and writing (BTQ) method in improving Islamic high school students’ Qur’an reading skills - Haldiati, Ayu Irda; Rosadi, Adi; Nurpalah, Muhammad Syamsudin; Heriyanto, Teguh (Risalah Kharisma, 2025)
This study addresses the critical issue of low Quranic reading proficiency among students at SMA Islam Miftahussa'adah, a secondary school in Indonesia, where preliminary data revealed significant deficiencies in fluency, tajwid application, and letter recognition. The primary objective was to analyze the effectiveness of the Quranic Reading and Writing (BTQ) method in enhancing students' ability to read the Quran correctly. Using a mixed-methods approach, the research combined a quasi-experimental design with qualitative data collection. A sample of 21 students was selected through random sampling, and data were gathered via validated questionnaires, participatory classroom observations, and in-depth interviews with both the teacher and students. The results demonstrated a 15% average improvement in overall Quranic reading ability, with notable gains in reading fluency (20%), mastery of makharijul huruf (18%), and understanding of tajwid (15%). Statistical analysis confirmed a significant positive correlation between the BTQ method and reading proficiency. In conclusion, while the BTQ method shows substantial potential, its effectiveness is heavily dependent on implementation quality, particularly regarding teaching methodology variation and media utilization. The study implies the necessity for comprehensive teacher training in diverse pedagogical strategies and the integration of digital learning tools to optimize BTQ instruction and address the multifaceted challenges of contemporary Islamic education.